1982
DOI: 10.1073/pnas.79.13.4143
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of a movable genetic element, 297, into the T-A-T-A box for the H3 histone gene in Drosophila melanogaster.

Abstract: From a cloned library of Drosophila DNA, a recombinant phage was isolated which contained a nucleotide sequence homologous to both the histone gene and a movable genetic element, 297 [Saigo, K., Millstein, L. & Thomas, C.A., Jr. (1981) Cold Spring Harbor Symp. Quant. Biol. 45, 815-827]. We have determined the nucleotide sequences of the termini of 297 as well as its insertion site in the histone gene in the clone. Our results strongly suggest that (i) although 297 ends with typical long terminal repeats, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…It will be interesting to see whether other Ty1-copia group retrotransposons follow the consensus shown in Figure 2. No comparable consensus has yet been reported for the Ty1-copia group retrotransposons of other plants or kingdoms (Le et al 2000;Kaminker et al 2002), although TSD preferences are well known for Ty3-gypsy group retrotransposons of Drosophila and plants (Ikenaga and Saigo 1982;Jiang et al 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see whether other Ty1-copia group retrotransposons follow the consensus shown in Figure 2. No comparable consensus has yet been reported for the Ty1-copia group retrotransposons of other plants or kingdoms (Le et al 2000;Kaminker et al 2002), although TSD preferences are well known for Ty3-gypsy group retrotransposons of Drosophila and plants (Ikenaga and Saigo 1982;Jiang et al 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster (14), the Ty elements of Saccharomyces cerevisiae (13), and vertebrate retrovirus proviruses (20). In addition to the conservation in the organization of the different transcription signals between the LTRs of retroviruses and copialike elements, the latter ones also contain nucleotide sequences homologous to the tRNA primer binding site and purine-rich sequences, both necessary for the initiation of DNA synthesis in a retrovirus system (6,16,22). The organization of the protein-coding regions of these different elements nevertheless varies.…”
mentioning
confidence: 99%
“…See Collins and Rubin 1982). It is also suggested that insertion of the copia elements into TATA box of the histone gene may change the rate of transcription (Ikenaga and Saigo 1982). The mutations induced by transposons in the present experiment may be different from the regulatory system located in the adjacent region of the structural genes, since the mutation rate is extrememly high.…”
Section: Resultsmentioning
confidence: 66%